Is the Turkish current account deficit sustainable? - Osman Furkan Abbasoğlu; Ayşe İmrohoroğlu; Ayşe Kabukçuoğlu (Koç University-TÜSİAD Economic Research Forum (ERF), 2017)
During the 2011-2015 period, Turkey's current account deficit as a percentage of GDP was one of the largest among the OECD countries. In this paper, we examine if this deficit can be considered sustainable using the Engel and Rogers (2006) approach. In this framework, the current account of a country is determined by the expected discounted present value of its future share of world GDP relative to its current share. A country, whose income is anticipated to rise relative to the rest of the world is expected to borrow now and run a current account de cit. Our findings suggest that Turkey's current account deficit in 2015 may be considered sustainable if the Turkish economy's share in the world economy could continue to grow at rates similar to the past. The same approach, however, indicates that the current account deficit in 2011, at its peak, was unlikely to be sustainable.
Keywords: F32; F41; F43; 330; current account; open economy macroeconomics; growth